2016
DOI: 10.1192/bjpo.bp.116.003491
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin levels in adults with ADHD

Abstract: BackgroundMicronutrients containing vitamins are reported to reduce symptom levels in persons with attention-deficit hyperactivity disorder (ADHD), but data on vitamin levels in ADHD are sparse.AimsTo examine the relationship between vitamin concentrations, ADHD diagnosis and psychiatric symptoms in young adult ADHD patients and controls.MethodEight vitamins and the nicotine metabolite cotinine were analysed in serum samples from 133 ADHD patients and 131 controls aged between 18 and 40, who also reported ADHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 33 publications
(58 reference statements)
1
12
1
Order By: Relevance
“…The various steps of the kynurenine pathway are dependent on coenzymes, such as the activated form of vitamin B6, pyridoxal 5′-phosphate (PLP). One study found an inverse correlation between serum levels of vitamin B6 and ADHD including its symptom severity [94]. Similarly, Aarsland et al also observed a decrease in vitamin B6 in their patient group.…”
Section: Evidence Linking Microbiota To Adhdmentioning
confidence: 89%
“…The various steps of the kynurenine pathway are dependent on coenzymes, such as the activated form of vitamin B6, pyridoxal 5′-phosphate (PLP). One study found an inverse correlation between serum levels of vitamin B6 and ADHD including its symptom severity [94]. Similarly, Aarsland et al also observed a decrease in vitamin B6 in their patient group.…”
Section: Evidence Linking Microbiota To Adhdmentioning
confidence: 89%
“…With respect to vitamin status, previous studies have suggested a role of vitamin B12 and vitamin D in the pathogenesis of mental disorders in childhood and adolescence [14,15]. In addition, poor B-vitamins status has been associated with not only the ADHD diagnosis but also the symptom severity [31]. Vitamins B2, B6, B12, and folic acid may be part of underlying pathophysiology of ADHD, since they are coenzymes participating in the one-carbon metabolism and contributing to the provision of methyl group which is required for the formation of multiple neurotransmitters including serotonin [32].…”
Section: Discussionmentioning
confidence: 99%
“…One treatment that logically stems from these studies is providing children with ADHD the nutrients required for optimal brain functioning. A strong theoretical basis exists for supplementing children with ADHD with a broad‐spectrum of micronutrients (vitamins and minerals) ranging from: correcting inborn errors of metabolism that slow metabolic reactions (Ames, Elson‐Schwab, & Silver, ), addressing identified vitamin deficiencies present in people with ADHD (Landaas et al., ), improving the microbiome (Kaplan, Rucklidge, McLeod, & Romijn, ), correcting deficiencies present in western diets (Davis, ) and/or increasing the production of adenosine triphosphate (ATP), the energy source produced by mitochondria (Gardner & Boles, ). All of these hypothesized mechanisms of action support a broad‐spectrum of micronutrients as an intervention rather than any one nutrient (e.g.…”
Section: Introductionmentioning
confidence: 99%